2017
DOI: 10.18632/oncotarget.23796
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of NM23 (NME) metastasis suppressor histidine phosphorylation to its nucleoside diphosphate kinase, histidine protein kinase and motility suppression activities

Abstract: The NM23/NME gene was identified as a metastasis suppressor. It's re-expression inhibited cancer cell motility and suppressed metastasis, without effecting primary tumor size in multiple model systems. The mechanisms of NME suppression of motility and metastasis are incompletely known. Of particular interest, has been NME histidine 118 phosphorylation, involved in nucleoside diphosphate kinase (NDPK) and histidine protein kinase (HPK) activities. Using recently developed monoclonal antibodies to phosphohistidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…Based on earlier studies it has been suggested that pHis might be more abundant in proteins than expected 29 and the existence of His kinases and pHis phosphatases in human cells also implies the existence of non-conventional phosphorylation-based signaling systems [30][31][32][33] . Our work shows for the first time that under non-acidic conditions, an overall coverage of SONAte phosphopeptide enrichment using HAP can reveal more non-conventional than conventional phosphorylation sites ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Based on earlier studies it has been suggested that pHis might be more abundant in proteins than expected 29 and the existence of His kinases and pHis phosphatases in human cells also implies the existence of non-conventional phosphorylation-based signaling systems [30][31][32][33] . Our work shows for the first time that under non-acidic conditions, an overall coverage of SONAte phosphopeptide enrichment using HAP can reveal more non-conventional than conventional phosphorylation sites ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To distinguish between these two functions, the consequences of mutating Pro96 of NME1 has been investigated. Mutation of Pro96 to serine causes conformational changes in NME affecting its binding to protein substrates [114]. This mutation was first identified in Drosophila as the "killer of prune" mutation since it was lethal in combination with the prune gene mutation [115][116][117].…”
Section: Nme Protein Histidine Kinase Functions As Revealed By Mutagementioning
confidence: 99%
“…Therefore, mutation of H118 abrogates both nucleotide and protein kinase activity, and mutation of Pro96 compromises only its protein kinase activity [53]. Recent findings indicate that NME1 s ability to suppress motility depends on its protein kinase function, as neither mutant is able to inhibit migration of transfected MDA-MB-231 and MDA-MB-435 breast cancer cells [114]. Interestingly, migrating cells overexpressing NME1 had lower levels of its 1-pHis form compared to stationary cells.…”
Section: Nme Protein Histidine Kinase Functions As Revealed By Mutagementioning
confidence: 99%
“…This includes cell migration [29], growth and differentiation [20,30,31], signal transduction, transcriptional regulation [32,33], and apoptosis [34]. In addition, other molecular activities have been assigned to NM23/NDPKs, such as histidine-dependent protein kinase (histidine phosphotransferase) activity [35][36][37][38], unusual nuclease activity [39,40], and lipid bilayer-binding [41]. Taken together, multiple functions have been assigned to the NM23/NDPK protein family and many interaction partners were identified by different in vitro methods [29].Thus NM23 gene family display pleiotropic functions and their effect on metastatic progression might be contradictory in many cancers.…”
Section: Introduction: Nm23-h1 the First Metastasis Suppressormentioning
confidence: 99%